2015
DOI: 10.1039/c5cc03455h
|View full text |Cite
|
Sign up to set email alerts
|

Single crystalline tantalum oxychloride microcubes: controllable synthesis, formation mechanism and enhanced photocatalytic hydrogen production activity

Abstract: Single crystalline microcubes of a new tantalum compound, tantalum oxychloride (TaO2.18Cl0.64), have been fabricated hydrothermally in a concentrated aqueous solution of hydrochloric acid and acetic acid. They contain a superstructure and exhibit remarkably enhanced photocatalytic activities for hydrogen production due to the improved light harvest and facilitated charge transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Finally, in the last step 3), hollow Co 3 O 4 material was obtained by calcination of h‐CoOH in air. Cubic Ta 2 O 5 PSCs with active facets were obtained by calcination TaO 2.18 Cl 0.64 precursor under Ar gas 82,83. The calcination for the TaO 2.18 Cl 0.64 only caused an intralayer transition; the {001} facets were preserved because of the strong 180° TaOTa structure connecting the layers.…”
Section: Basic Features Of Pscsmentioning
confidence: 99%
“…Finally, in the last step 3), hollow Co 3 O 4 material was obtained by calcination of h‐CoOH in air. Cubic Ta 2 O 5 PSCs with active facets were obtained by calcination TaO 2.18 Cl 0.64 precursor under Ar gas 82,83. The calcination for the TaO 2.18 Cl 0.64 only caused an intralayer transition; the {001} facets were preserved because of the strong 180° TaOTa structure connecting the layers.…”
Section: Basic Features Of Pscsmentioning
confidence: 99%
“…30,31 The recent demonstration of a new efficient tantalum oxide photocatalyst TaO 2.18 Cl 0.64 for hydrogen production indicates that changing chemical compositions and crystal structures of tantalum oxides is an alternative means to enhance photocatalytic activities, which plays an important role in improving charge transfer and making the flat-band potential more negative. 16 As reported, F − ion doping not only increases the charge separation efficiencies, but also improves the light harvest in UV−vis region under the condition of almost remaining the reduction abilities of photogenerated electrons. 30,32−35 For tantalum oxyfluorides involving Ta 3 O 7 F and TaO 2 F, the incorporation of F − ions may improve the photocatalytic activity by modulating the crystal structure and composition.…”
Section: ■ Introductionmentioning
confidence: 75%
“…In Figure 2b, the doublet peaks centered at 26.3 and 28.2 eV are assigned to Ta 4f 7/2 and Ta 4f 5/2 orbitals, respectively, revealing that the oxidation state of Ta is identical to that of tantalum oxides. 16 The XPS spectrum of F 1s core electrons has a peak centered at 684.5 eV, originated from Ta−F bonds on the surface of tantalum oxyfluoride ACHNs. 29,39 The other F 1s peak at 689.0 eV is assigned to the substitutional F atoms that occupied oxygen sites in the lattice and formed Ta−F−Ta bonds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Wan et al reported that Ta sub-oxide (TaOx) is a promising electron selective contact for crystalline Si photovoltaics and photo-electrochemical water reduction [27]. Tantalum oxynitride (TaON) [28], dioxychloride (TaO2Cl) [29], and dioxyfluoride (TaO2F) [30], and the MXene family member tantalum hemicarbide (Ta2C) [31], are excellent electrocatalysts for several catalytic reactions because of their suitable optical bandgap and superior charge transfer rates. Among these electrocatalysts, TaO2F is the most stable inorganic compound found in nature because it exhibits the highest known melting points of all existing materials [30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Tantalum oxynitride (TaON) [28], dioxychloride (TaO2Cl) [29], and dioxyfluoride (TaO2F) [30], and the MXene family member tantalum hemicarbide (Ta2C) [31], are excellent electrocatalysts for several catalytic reactions because of their suitable optical bandgap and superior charge transfer rates. Among these electrocatalysts, TaO2F is the most stable inorganic compound found in nature because it exhibits the highest known melting points of all existing materials [30,32]. Furthermore, carbon (C) doping has been proven to improve the stability and the light harvesting and charge separation efficiency of many compounds possessing photocatalytic activity [33,34].…”
Section: Introductionmentioning
confidence: 99%